Characteristics of Faecal Microbiota in Paediatric Crohn's Disease and Their Dynamic Changes During Infliximab Therapy. (29th November 2017) - Wang, Yizhong; Gao, Xuefeng; Ghozlane, Amine; Hu, Hui; Li, Xiaolu; Xiao, Yongmei; Li, Dan; Yu, Guangjun; Zhang, Ting
Abstract: Background: Crohn's disease [CD] is known to be associated with gut microbial dysbiosis. Infliximab [IFX] is increasingly used to treat paediatric CD; however, it is not clear how the gut microbiota is modified during IFX treatment. The aim of this study was to characterise the faecal microbiota community composition in paediatric CD patients and to assess its dynamic changes during IFX therapy. Methods: A 16S rRNA sequencing approach was applied to determine the compositions of microbial communities in faecal samples. The composition and function of the faecal microbiota were compared between CD patients and healthy controls. Results: Characteristics of faecal microbiome composition in paediatric CD patients before IFX treatment were represented by a lower biodiversity, a gain in Enterococcus, and a significant loss in multiple short-chain fatty acid [SCFA]-producing bacteria, including Anaerostipes, Blautia, Coprococcus, Faecalibacterium, Lachnospira, Odoribacter, Roseburia, Ruminococcus, and Sutterella . Additionally, alterations were observed in metabolic functions of the gut microbial community in CD. IFX treatment increased the biodiversity of gut microbiota and shifted its composition as well as its functional capabilities in the paediatric CD patients toward a healthy status. However, multiple SCFA-producing taxa were not significantly expanded. The sustained response of paediatric CD patients to IFX was associated with abundance of SCFA-producing bacteria. Conclusions: A lower biodiversity with alterations in the composition and function of faecal microbial community, characterising gut microbial dysbiosis, was observed in Chinese paediatric CD patients. IFX diminished the CD-associated gut microbial dysbiosis but was deficient in increasing certain SCFA-producing taxa.